Oral Delivery of Liraglutide-Loaded Zein/Eudragit-Chitosan Nanoparticles Provides Pharmacokinetic and Glycemic Outcomes Comparable to Its Subcutaneous Injection in Rats - Ziebarth, Jeferson; da Silva, Letícia Marina; Lorenzett, Ariane Krause Padilha; Figueiredo, Ingrid Delbone [UNESP]; Carlstrom, Paulo Fernando [UNESP]; Cardoso, Felipe Nunes [UNESP]; de Freitas, André Luiz Ferreira [UNESP]; Baviera, Amanda Martins [UNESP]; Mainardes, Rubiana Mara (MDPI, 2024)
Liraglutide (LIRA) is a glucagon-like peptide-1 (GLP-1) receptor agonist renowned for its efficacy in treating type 2 diabetes mellitus (T2DM) and is typically administered via subcutaneous injections. Oral delivery, although more desirable for being painless and potentially enhancing patient adherence, is challenged by the peptide’s low bioavailability and vulnerability to digestive enzymes. This study aimed to develop LIRA-containing zein-based nanoparticles stabilized with eudragit RS100 and chitosan for oral use (Z-ERS-CS/LIRA). These nanoparticles demonstrated a spherical shape, with a mean diameter of 238.6 nm, a polydispersity index of 0.099, a zeta potential of +40.9 mV, and an encapsulation efficiency of 41%. In vitro release studies indicated a prolonged release, with up to 61% of LIRA released over 24 h. Notably, the nanoparticles showed considerable resistance and stability in simulated gastric and intestinal fluids, suggesting protection from pH and enzymatic degradation. Pharmacokinetic analysis revealed that orally administered Z-ERS-CS/LIRA paralleled the pharmacokinetic profile seen with subcutaneously delivered LIRA. Furthermore, in vivo tests on a diabetic rat model showed that Z-ERS-CS/LIRA significantly controlled glucose levels, comparable to the results observed with free LIRA. The findings underscore Z-ERS-CS/LIRA nanoparticles as a promising approach for oral LIRA delivery in T2DM management.
Keywords: glucagon-like peptide-1; oral bioavailability; type 2 diabetes mellitus; zein nanoparticles